Integrating Hospital Information Systems and National Health Insurance: Impact on Employee Performance and Service Quality - Nining Handayani; M. Yani Syafei; Umi Narimawati (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Indonesia’s healthcare system is undergoing a digital transformation through the integration of the Hospital Management Information System and the national health insurance platform. These systems aim to enhance operational efficiency and healthcare access but face challenges in specialized settings like military dental hospitals. This study examines the impact of integrating these systems on employee performance and service quality at the Dental and Oral Hospital of the Indonesian Navy R.E. Martadinata in Jakarta. Using a qualitative case study approach, data were gathered through literature reviews and institutional observations to identify operational and systemic barriers. The findings highlight issues such as limited digital literacy among staff, inconsistent system use, and administrative delays that hinder optimal service delivery and efficiency. These challenges are intensified by the unique operational context of military hospitals. The study concludes that improving the integration of these systems requires targeted staff training, robust digital infrastructure, and cohesive policy support to align technology with institutional needs and patient-centered care priorities, ultimately enhancing service quality and employee performance in specialized healthcare settings.